Impact of Hyperbaric Oxygenation on Ammonia Kinetics in Hepatic Failure (an Experimental Study) - P. N. Savilov; D.V. Molchanov; A. A. Alabovsky (Общая реаниматология)
Objective: to study ammonia kinetics in hepatic failure and in the course use of hyperbaric oxygenation (HBO) sessions. Material and methods. Experiments were carried out on 210 female albino rats. HBO was thrice conducted at 3 ata for 50 min once daily after hepatectomy (HE, 15—20% of the liver mass). Ammonium levels were determined in the visceral organs and blood from the following vessels: the aorta, v. porta, v. hepatica, v. renalis. Results. By preventing ammonia from entering the central bloodstream from the remaining postresection liver part and by restoring its ammonia-absorbing capacity, HBO creates conditions for eliminating arterial hyperammoniemia. HBO prolongs the inhibitory impact of HE on the entrance of ammonia from the gastrointestinal organs into the portal circulation, by preventing its selective accumulation in them, and decreases renal tissue ammonia concentrations. HBO keeps ammonia from being accumulated by cerebral cortical neurons, limits its lung accumulation, and creates conditions for its active neutralization by splenocytes in the posthy-peroxic period (PHP). At the same time HBO induces short-term activation of ammoniogenesis in thyroid and cardiac tissues, which should be considered as a sign of their enhanced functional activity. Conclusion. Hyperbaric oxygen eliminates ammonia kinetic disorders in the operated organism in HE-induced hepatic failure. The therapeutic effect of HBO remained by days 11 post-PHP. Key words: hyperoxia, ammonia, exchange, hepatic failure, organism, metabolism.